2022
DOI: 10.3390/ijms23063066
|View full text |Cite
|
Sign up to set email alerts
|

Dysfunctional cGMP Signaling Leads to Age-Related Retinal Vascular Alterations and Astrocyte Remodeling in Mice

Abstract: The nitric oxide–guanylyl cyclase-1–cyclic guanylate monophosphate (NO–GC-1–cGMP) pathway is integral to the control of vascular tone and morphology. Mice lacking the alpha catalytic domain of guanylate cyclase (GC1−/−) develop retinal ganglion cell (RGC) degeneration with age, with only modest fluctuations in intraocular pressure (IOP). Increasing the bioavailability of cGMP in GC1−/− mice prevents neurodegeneration independently of IOP, suggesting alternative mechanisms of retinal neurodegeneration. In conti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
9
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

3
2

Authors

Journals

citations
Cited by 6 publications
(9 citation statements)
references
References 53 publications
0
9
0
Order By: Relevance
“…Mice lacking the alpha catalytic subunit of guanylate cyclase ( GC1 −/− ) were considered a novel murine model of POAG; the mice exhibit degeneration of RGCs with age, without large increases in IOP and an open irideocorneal angle [ 26 ]. GC1 −/− mice also develop retinal vascular dysfunction and aberrant retinal vascular morphology with age, and astrocyte morphology alterations precede vascular abnormalities [ 29 ]. These results suggest that NO-cGMP signaling functions to maintain homeostasis in cells of the NVU, and thus the NO-cGMP pathway remains an attractive area of investigation for glaucoma.…”
Section: No-cgmp Signaling In Glaucomamentioning
confidence: 99%
See 4 more Smart Citations
“…Mice lacking the alpha catalytic subunit of guanylate cyclase ( GC1 −/− ) were considered a novel murine model of POAG; the mice exhibit degeneration of RGCs with age, without large increases in IOP and an open irideocorneal angle [ 26 ]. GC1 −/− mice also develop retinal vascular dysfunction and aberrant retinal vascular morphology with age, and astrocyte morphology alterations precede vascular abnormalities [ 29 ]. These results suggest that NO-cGMP signaling functions to maintain homeostasis in cells of the NVU, and thus the NO-cGMP pathway remains an attractive area of investigation for glaucoma.…”
Section: No-cgmp Signaling In Glaucomamentioning
confidence: 99%
“…In focal brain injury, inhibiting PDE increased cGMP and altered the glial inflammatory response, decreased oxidative stress and cell death, and increased angiogenesis ( Figure 3 ) [ 84 ]. A potential role for cGMP signaling in retinal astrocyte physiology has been reported in a study using a germline GC1 alpha subunit knockout mouse [ 29 ]. In the study, GC1 −/− mice that developed RGC degeneration with age [ 26 , 28 ] were shown to have an altered retinal vascular phenotype; blood vessels in the peripheral retinal vasculature were dilated and exhibited shorter capillary branching [ 9 , 29 ].…”
Section: No-cgmp Signaling In Glial Cellsmentioning
confidence: 99%
See 3 more Smart Citations